PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM MENDORONG HAK PEKERJA MIGRAN MELALUI PROGRAM SAFE AND FAIR DI INDONESIA - Hutagaol, Princess Restauli; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study examines the role of the International Labour Organization (ILO) in promoting the rights of Indonesian migrant workers through the Safe and Fair: Realizing Women Migrant Workers’ Rights and Opportunities in the ASEAN Region program implemented in Indonesia from 2018 to 2023. The research is grounded in the persistent vulnerability of Indonesian migrant workers, particularly women, who face gender-based violence, exploitation, and human rights violations, exacerbated by limited access to skills training, accurate information, and comprehensive protection mechanisms. Using Clive Archer’s theory of international organizations—instrument, arena, and actor—the study focuses on ILO’s role as an arena that brings together multiple stakeholders to strengthen gender-responsive migration governance. The findings reveal that ILO, through Safe and Fair, significantly contributes to fulfilling three core rights mandated by Article 6 paragraph (1) of Law No. 18 of 2017: capacity building, access to accurate information, and human rights protection throughout the migration cycle. These contributions include strengthening pre-departure training curricula, providing multilingual educational materials, conducting public campaigns, supporting policy reform, and developing the LTSA–MRC integrated service model that combines administrative processes with social and legal support. The study concludes that ILO’s role as an arena effectively enhances multi-stakeholder coordination and promotes safer, fairer, and more sustainable migration governance for Indonesian migrant workers. Keywords: ILO, Safe and Fair, Indonesian migrant workers, human rights, Clive Archer, Law No. 18 of 2017, women migration.